Efficient sampling strategies for assessing the prognostic value of a new biomarker at a temporal endpoint - Hani Samawi; Haresh Rochani (Research in Statistics)
In this research, we introduce an enhanced sampling methodology for the recruitment of subjects in survival analysis. This approach incorporates Moving Extreme Ranked Set Sampling and Ranked Set Sampling schemes, employing a ranking based on survival time during the initial phase of a two-phase evaluation. The study focuses on assessing the prognostic value of new biomarkers on a time-to-event parameter using a Cox-weighted model, where the inverse of empirical inclusion determines weights. A comprehensive simulation-based analysis underscores the efficacy of this sampling plan, revealing a more potent testing procedure and efficient estimation of hazard ratios compared to conventional methods such as simple random sampling (SRS) and other existing sampling schemes.